2011
DOI: 10.3844/ajassp.2011.407.412
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and Beta Carotene Composition in Four Different Vegetable Oils

Abstract: Problem statement: Some vegetable oils contains natural antioxidants such as beta carotene and vitamin E namely tocopherol and tocotrienol. Different vegetable oils contained different amount of vitamin E and β-carotene. Approach: Study was carried out to investigate the natural antioxidants (vitamin E and beta carotene) composition in four different vegetable oils [Red Palm Olein (RPO), palm plein (PO), Corn Oil (CO) and Coconut Oil (COC)]. Results: The results showed that RPO contained the highest amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Quantification of tocols was calculated based on the following formula obtained from Dauqan et al . [29] and was reported as mg of tocols/g of TRF: Tocols concentration (ppm) = As/Astd × Vs/Ws × Cstd × VIstd/Vis where As = Area of sample; Astd = Area of standard; Vs = Volume of sample; Ws = Weight of sample; Cstd = Concentration of standard; VIstd = Volume of standard injected; Vis = Volume of sample injected.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of tocols was calculated based on the following formula obtained from Dauqan et al . [29] and was reported as mg of tocols/g of TRF: Tocols concentration (ppm) = As/Astd × Vs/Ws × Cstd × VIstd/Vis where As = Area of sample; Astd = Area of standard; Vs = Volume of sample; Ws = Weight of sample; Cstd = Concentration of standard; VIstd = Volume of standard injected; Vis = Volume of sample injected.…”
Section: Methodsmentioning
confidence: 99%
“…Tocopherols and tocotrienols are the major fat-soluble anti-oxidants in vegetable oils (18). Dauqan et al (19) reported that the content and the percent composition of tocopherols and tocotrienols were higher in palm oil and red palm oil compared to corn oil. The β-carotene content is the highest in red palm oil and the lowest in corn oil (19).…”
Section: Introductionmentioning
confidence: 99%
“…Dauqan et al (19) reported that the content and the percent composition of tocopherols and tocotrienols were higher in palm oil and red palm oil compared to corn oil. The β-carotene content is the highest in red palm oil and the lowest in corn oil (19). Napolitano et al (12) suggested that the anti-oxidant properties of vegetable oils from different sources have to be considered when analysing acrylamide formation.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned by Scott (2001), CPO shows three absorption maxima similar to pure β -carotene at 425, 450 and 478 nm (Figure 2). Palm olein does not show any absorption peaks within 400-500 nm range which proves that β -carotene level in palm olein is less than detectable limit (Top et al 2011).…”
Section: Carotenoids Analysismentioning
confidence: 92%